Cardiac diseases among liver transplant candidates. Issue 7 (19th June 2018) - Gitman, Marina; Albertz, Megan; Nicolau‐Raducu, Ramona; Aniskevich, Stephen; Pai, Sher‐Lu
Abstract: Improvements in early survival after liver transplant (LT) have allowed for the selection of LT candidates with multiple comorbidities. Cardiovascular disease is a major contributor to post‐LT complications. We performed a literature search to identify the causes of cardiac disease in the LT population and to describe techniques for diagnosis and perioperative management. As no definite guidelines for preoperative assessment (except for pulmonary heart disease) are currently available, we recommend an algorithm for preoperative cardiac work‐up.